The Impact of the Physiochemical Properties of Manufactured Nanoparticles on In vitro and In vivo Evaluation of Particle Toxicity - Horie, Masanori; Iwahashi, Hitoshi (My University, 2014)
Recently, many in vitro studies evaluating the effects of nanoparticles on cellular physiology have been reported. In in vitro systems, the nano-objects induce not only primary effects but also confounding (artificial) effects. Investigations into the physiological and pathological effects induced in cells by in vitro exposure to nano-objects may be confounded by the specific physical and chemical properties of the objects. For example, protein adsorption from the culture media to the surfaces of nano-objects can essentially starve the cells. In addition, certain nanoparticles can release metal ions into cell culture or bioassay reagents. The protein adsorption and metal ion release by the nano-objects can interfere with ELISA and LDH assays, producing inaccurate results. Moreover, unstable or non-homogenous suspensions of nano-objects can result in imprecise in vitro evaluations of nano-objects. For accurate in vitro testing of nanoparticles, we should consider the effects of these three important properties of nanosuspensions: protein adsorption, metal ion release, and suspension stability.
Keywords: Nano-object; Nanosuspension; Adsorption; Metal ion; Suspension stability